Modelling of Faulty Three Phase Induction Motor by Field Orientation - M. Jannati; N. R. N. Idris; M. J. A. Aziz (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
This study investigates the simple vector control of a 3-phase squirrel cage Induction Motor (IM) under open-circuit fault (faulty 3-phase IM). It was shown that it is needed to supply the stator windings with unbalanced currents to remove the oscillating term of the machine electromagnetic torque. The vector control system is based upon Field-Oriented Control (FOC) that has been adapted for this type of machine. Simulation results are provided to show the operation of the proposed drive system.